Optimal rates of convergence of some iterative approximation methods for the solution of fredholm equations in spaces of periodic analytic functions - Askarov, M.; Pereverzev, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider some classes of Fredholm equations with integral operators acting in spaces of periodic analytic functions. For these classes, we establish the exact order of the optimal rates of convergence for some versions of the method of iterative projections and KP methods.